Monitoring of the state of health of students of Kharkov institutes of higher - Баламутова [Nataliya Balamutova] Наталія Михайлівна; Коломійцева [Olga Kolomiytseva] Ольга Едуардівна (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> The questions of estimation of the state of health of students are considered on the basis of study of indexes of the cardiovascular system. For the estimation of the functional state of the cardiovascular system one of the most widespread methods was used is measuring of arteriotony. 1500 students of the Kharkov institutes of higher took part in an experiment. It is educed, that greater part of different diseases for students is bound by c violation of functions of the cardiovascular system. It is set that the number of rejections in a state of health of students grows from a course to the course. In this connection forming of task medical forces is required for work with students, having cardiologic diseases. <!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>